Reality Television and Audience Dilemma for Big Brother Naija Survival in Nigeria - Stanislaus Iyorza (PREDESTINASI, 2021)
The Big Brother Naija show is a reality television programme in Nigeria that premiered first in the year 2006, a programmein Nigeria that admits between 12 and 21 housemates for a period of 3 weeks to evoke certain characteristics from them. From inception, the show has attracted wide condemnation over acts of indecency and immorality among the housemates, while some audiences feel the program still has some benefits to the housemates, the audiences and Nigeria as a whole. Consequently, the call for ban of the program in some quarters as well as the support for the survival of same places the audience of the show in a dilemma. The objectives of this paper include to ascertain the benefits or values of the Big Brother Naijaprogramme to the housemates and audiences and to determine the audiences’ position on the survival or proscription of the show. This study is supported by a framework of Uses and Gratification Theory and the Social Learning Theory. Under the quantitative research method employed in this study, the survey design was adopted for a sample population of 460 respondents. Findings show that audiences largely accept that the show has value to the social and economic status of the housemates with little value to educational and emotional needs of the audience despite its fairly significant entertainment value.More respondents agreed to the indecent and corrupt nature of the Big BrotherNaija with a little more than of half of the population calling for its ban. The study concludes that the ban of the show was not necessary as this will negate all the benefits. The paper recommends that producers of the show should consciously introduce rules that will mitigate core acts of indecency and immorality among the housemates while members who find the program distasteful should avoid tuning to the channels.